Hubungan Antara Kepuasan Hidup Dengan Fear of Missing Out (FoMO) Pengguna Media Sosial pada Mahasiswa di Kota Medan - Paskalis Lewis Panjaitan; Nenny Ika Putri Simarmata (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the relationship between life satisfaction and fear of missing out (FoMO) among college students using social media in Medan City. This study used a quantitative approach with a correlational design. The study subjects were 385 students selected using a purposive sampling technique. Data were collected through life satisfaction and FoMO scales, then analyzed using the Spearman's rho correlation test because the data did not meet the assumption of a normal distribution. The results showed a negative and significant relationship between life satisfaction and FoMO with a correlation coefficient value of -0.201 and a significance level of 0.000 (p < 0.05). This finding indicates that the higher the student's life satisfaction, the lower the tendency to experience FoMO. Based on empirical categorization, students have a high level of life satisfaction and FoMO in the moderate category. Although the relationship between the two variables is relatively weak, this study contributes to understanding the psychological factors related to social media usage behavior in college students, particularly the importance of increasing life satisfaction as one aspect that can support the management of FoMO tendencies.